Selling through someone else : how to use agile sales networks and partners to sell more - Wollan, Robert (John Wiley & Sons, 2013)
Experience the growth multiplier effect through transforming the distribution and sales network Selling Through Someone Else tackles new opportunities to drive company growth by taking a fresh look at the customer smart distribution and sales process. The authors, from Accenture, one of the world's largest consulting companies, explain how companies can be smarter about what their customers truly want and maximize the return on investment from all available resources for growth opportunities by exploring creative distribution options, including leveraging partners, online outle.